FORMATIVE AND SUMMATIVE ASSESSMENT IN FOREIGN LANGUAGE LEARNING - Orazimbetov Shingisbek; Orakbaeva Shirin (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract; This paper discusses the role of assessment in foreign language learning, focusing on formative and summative approaches. It highlights how assessment supports teaching and learning by providing feedback, improving motivation, and identifying learners’ strengths and weaknesses. The study shows that clear criteria and continuous assessment improve student performance and engagement. It also explains the shift from traditional grade-based assessment to a more learner-centered approach that encourages active participation, self-development, and better language acquisition outcomes in modern education.